Eco-Biofriendly digital magazine : promoting situated writing process skills. (2023)
The current research was conducted at Instituto Pedagógico Nacional with 29 eighth grade students, whose ages range from 13 to 15 years old. This research aimed to describe how the use of the writing process approach might shapes situated writing skills in EFL through the creation of an environmental awareness digital magazine. Consequently, this research was held under the principles of action research and followed the writing process approach, situating writing as a social practice, from a set of writing-based activities to improve students' EFL skills in order to achieve the writing of a paragraph based on their environmental experiences to make a digital magazine. That is why, this proposal was organized in 3 cycles, to be implemented along 12 interventions; during which surveys, field notes, artifacts and interviews were applied as instruments to collect data. Finally, through the grounded approach, it was possible to analyze the findings and present the categories, conclusions, implications and limitations of the project.